Johanna Lessinger.
This paper explains the trends in sexual division of labor by femini st social scientists and was written by Johanna Lessinger of Research I nstitute for the study of man, New York however the title was not inclu ded on the paper.
AR/MISR/33/1/13
English
Shelf no. 1.
Keywords: Sexual division of labor